2014
DOI: 10.1111/1750-3841.12534
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Poly(Lactic Acid)‐Based Materials for Antimicrobial Packaging

Abstract: Poly(lactic acid) (PLA) can be synthesized from renewable bio-derived monomers and, as such, it is an alternative to conventional petroleum-based polymers. Since PLA is a relatively new polymer, much effort has been directed toward its development in order to make it an acceptable and effective option to the more traditional petroleumbased polymers. Commercially, PLA has received considerable attention in food packaging applications with a focus on films and coatings that are suitable for short shelf life and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
142
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(148 citation statements)
references
References 128 publications
3
142
0
3
Order By: Relevance
“…Poly(lactic acid) is a polymer from renewable sources and derived from lactic acid esterification process from fermentation of bacteria by using starch substrate or simple sugar. Poly(lactic acid) has a heat resistance, strong and elastic polymer [1]. Poly(lactic acid) packaging can be used to package various foodstuff, one of which was tea drink.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(lactic acid) is a polymer from renewable sources and derived from lactic acid esterification process from fermentation of bacteria by using starch substrate or simple sugar. Poly(lactic acid) has a heat resistance, strong and elastic polymer [1]. Poly(lactic acid) packaging can be used to package various foodstuff, one of which was tea drink.…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been implemented to impart these properties into the plastics. For example, teams have triedcoating the plastics with an active agent (Salmieri et al 2014, Tawakkal et al 2014, inserting sachets into the packaged goods (Tian et al 2013), and inserting bioactive component into the packaging material itself . Given that the phenomenon of bacterial contamination is a surface based mechanism, it is in our best opinion that incorporation of the bioactive agent into the film will impart many advantages when compared to the other strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been found that the above drawbacks can be overcome by the addition of an appropriate filler (7)(8)(9)(10)(11)(12)(13)(14). Many studies have been conducted to provide PLA with antimicrobial properties that might encourage its use in active food packaging as well as in specific biomedical applications (15)(16)(17)(18)(19)(20). Controlled drug delivery systems are attracting increasing attention in the biomedical and pharmaceutical sectors (21)(22).…”
Section: Introductionmentioning
confidence: 99%